Permasalahan Kesehatan Masyarakat Pedesaan dan Upaya Perbaikannya - Putri Fakhira Lubis; Usiono Usiono (JOURNAL SAINS STUDENT RESEARCH, 2024)
Health status is increasingly declining in the community, especially rural communities. Public Health Problems are global challenges that are often influenced by social, economic and environmental factors. Some of the health problems of rural communities are limited access to health services, low number of families participating in family planning programs, higher poverty rates, and many residents who do not have health insurance. Efforts to overcome this problem are by promoting health education through outreach programs that focus on disease prevention, increasing access to health services through government policies, and providing information to rural communities about the importance of creating a healthy environment. The design of this research is a Systematic Literature Review based on journal references. Through these prevention efforts, it is hoped that rural community health problems can be resolved and the quality of life of rural communities can improve significantly.